2018
DOI: 10.1136/bjsports-2018-099029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular screening of Olympic athletes reported by chief medical officers of the Rio 2016 Olympic Games

Abstract: Most of the responding countries perform annual cardiovascular screening of Olympic athletes, but there are differences in the components used. Athletes from countries with larger athlete delegations and higher GDP per capita were more likely to be screened with ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…This makes the detection of clinically relevant conditions among athletes competing at international championships a real challenge. Similarly to a study conducted at the Rio Olympics, 11 we found a large difference in PPCE prevalence between athletes from LMICs (28%) and VHICs (74%). We also found that the TTE prevalence among African athletes was low (4%).…”
Section: Discussionsupporting
confidence: 83%
“…This makes the detection of clinically relevant conditions among athletes competing at international championships a real challenge. Similarly to a study conducted at the Rio Olympics, 11 we found a large difference in PPCE prevalence between athletes from LMICs (28%) and VHICs (74%). We also found that the TTE prevalence among African athletes was low (4%).…”
Section: Discussionsupporting
confidence: 83%
“…This finding may reflect the increased risk for CV disease in Paralympic athletes, possibly attributable to higher prevalence of CV disorders, structural cardiac adaptations that result from haemodynamic alterations in spinal cord-injured or amputee athletes, or increased risk of coronary disease due to a relative decrease in overall physical activity 5–7. The proportion of Paralympic athletes screened for CV disease is higher than Olympic athletes, with 92.3% vs 79.8% screened with personal history, family history and physical exam, as well as 84.6% vs 74.5% with ECG 4. Furthermore, athletes with SCI may have difficulty describing symptoms of angina due to decreased sensory feedback.…”
mentioning
confidence: 99%
“…In 2009, the IOC presented the Consensus Statement on PHE of elite athletes 8) , which proposed the investigation of cardiovascular abnormalities, including family history, personal history, physical examination, and (Figure-4). However, as described in the study by Toresdahl et al above, in the 2016 Rio Olympic Games, many of the surveyed countries still had no screening for personal history (13.8% of countries did not screen), family history (14.9%), physical examination (12.8%), or resting ECG (25.5%) 26) . Pelliccia and Drezner mentioned that "expanding education and training in sports cardiology will allow broader implementation of the current guidelines to optimize the cardiovascular care of Olympic athletes and move toward a more uniform standard"in their Editorial Comments 29) .…”
Section: Periodic Health Evaluation (Phe) For Participants Of Olympicmentioning
confidence: 95%
“…These cardiac events are often asymptomatic prior to their ). Athletes were more likely to be screened with ECG in countries with a relatively larger athlete delegation (OR 2.05, p = 0.023) and with higher Gross Domestic Product per capita (OR 1.69, p = 0.014) 26) (Figure-3).…”
Section: Periodic Health Evaluation (Phe) For Participants Of Olympicmentioning
confidence: 99%